PROSES INFERENSI PADA MODEL LOGIT - Rusgiyono, Agus (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2008)
Let represent the response on a nominal random variable of Bernoulli distribution, with , where is a parameter with unknown value. Problems of estimating used smallest square methods in linier regression model can overcome with used maximum likelihood method in logistic regression.. Suppose is maksimum likelihood estimstors of . In case can be obtained from first condition, ln(Ln(p)) to be maximum at point then be obtained and that is unbiased estimator because To be test hipothesis that , with a large sample size used fact that Keywords : Estimator, unbiased estimator, test statistic